The maternal X chromosome affects cognition and brain ageing in female mice - Samira Abdulai-Saiku; Shweta Gupta; Dan Wang; Francesca Marino; Arturo J. Moreno; Yu Huang; Deepak Srivastava; Barbara Panning; Dena B. Dubal (Nature, 2025)
Abstract Female mammalian cells have two X chromosomes, one of maternal origin and one of paternal origin. During development, one X chromosome randomly becomes inactivated 1–4 . This renders either the maternal X (X m ) chromosome or the paternal X (X p ) chromosome inactive, causing X mosaicism that varies between female individuals, with some showing considerable or complete skew of the X chromosome that remains active 5–7 . Parent-of-X origin can modify epigenetics through DNA methylation 8,9 and possibly gene expression; thus, mosaicism could buffer dysregulated processes in ageing and disease. However, whether X skew or its mosaicism alters functions in female individuals is largely unknown. Here we tested whether skew towards an active X m chromosome influences the brain and body—and then delineated unique features of X m neurons and X p neurons. An active X m chromosome impaired cognition in female mice throughout the lifespan and led to worsened cognition with age. Cognitive deficits were accompanied by X m -mediated acceleration of biological or epigenetic ageing of the hippocampus, a key centre for learning and memory, in female mice. Several genes were imprinted on the X m chromosome of hippocampal neurons, suggesting silenced cognitive loci. CRISPR-mediated activation of X m -imprinted genes improved cognition in ageing female mice. Thus, the X m chromosome impaired cognition, accelerated brain ageing and silenced genes that contribute to cognition in ageing. Understanding how X m impairs brain function could lead to an improved understanding of heterogeneity in cognitive health in female individuals and to X-chromosome-derived pathways that protect against cognitive deficits and brain ageing.